Implementation of the Context, Input, Process, Product Model in Evaluating Islamic Education Institutions - Nuha, Nazahah Ulin; Faridi, Achmad; Tobroni, Tobroni (International Journal of Islamic Studies Higher Education, 2024)
Institutional evaluation in Islamic education has an important role in improving the quality of education. Evaluation not only focuses on learning outcomes, but also analyzes various aspects of the education system, including curriculum, teaching methods, and institutional management. So it aims to integrate Islamic values in educational evaluation using the Context, Input, Process, Product model. This approach is expected to create a holistic evaluation that is balanced between academic and spiritual dimensions, while contributing to the development of Islam-based education. This article uses a qualitative method with a content analysis approach to collect and analyze information related to institutional evaluation. Data were obtained from various sources, such as books, research articles, and scientific journals relevant to institutional evaluation, then analyzed using Miles and Huberman's thematic data analysis technique. The main idea of the article Integration of Islamic values of context, input, process, product model in educational evaluation is to adapt the context, input, process, and product evaluation model by integrating Islamic values. This aims to create an educational evaluation system that is not only oriented towards academic aspects, but also builds Islamic character. This article offers a holistic evaluation framework that combines modern approaches with Islamic spiritual and moral principles to improve the overall quality of education.